Analysing the safety work culture in the manufacturing industry / Khairunnisa' Yussof - Yussof, Khairunnisa' (2017)
Safety work culture has become a significant aspect in an organisation especially in manufacturing industry. However, the higher numbers of accident reported was in manufacturing industry. A strong safety work culture needs to be developed in order to enhance the effectiveness of risk management. This study aims to analyse the safety work culture in manufacturing industry and for this purpose, electrical and electronics (E&E) sector in Pulau Pinang was chosen as the scope of study. Questionnaires were distributed to 379 employees employed in this sector. Several variables i.e leadership's roles, employee engagement, strategic communication, organisation design were examined against the safety work culture. The findings revealed that all these variables were significant with the exception of organisation design and strategic communication, in influencing safety work culture in organisations. The results indicated that employees' and leadership roles are important to maintain a strong safety work culture in manufacturing sector. Employee engagement was found to be the most significant factor contributing to safety work culture as it can develop understanding among employees about the importance of their roles towards safety work culture. The results also provide useful inputs in guiding manufacturing management and risk practitioners to re-evaluate existing policies and guidelines to create an effective safety work culture in manufacturing sector.